Analysis of factors involved in preventive medical appointments. Case of Bogota, Colombia 2014 - Pardo Ruiz, Ricardo José; Chaparro Escobar, Nelson Arturo (Población y Salud en Mesoamérica, 2017)
Objective: Analyze factors involved in preventive medical appointments attendance in Bogota year 2014. Methods: two models were adjusted under GEE using a Bernoulli link function with independent and exchangeable correlation structures for preventive medical appointments attendance. Results: Income and socioeconomic stratum increase probability of preventive appointments attendance: Odds ratio of attendance and not attendance is at least 1,5 times higher in stratum 2 or higher households. Also, for every $100.000 additional pesos in monthly household income the reason increases by 1%. Household members which head reached an educational level higher than primary have an odds ratio of attendance and not attendance up to 2,3 times higher. Conclusions: Results are similar to Grossman (1972) and Kenkel (1990) nevertheless, individual educational level, presence in household of elder people or children and even presence of spouse are not related with preventive medical appointments attendance.